Foro sobre Eutanasia - García Quiroz, Javier Mauricio; López Ríos, Rosemary; Uribe Ángel, Marco Tulio; Yepes García, John Edward (Estudios de Derecho, 1997)
Foro realizado dentro del curso de Filosofia del Derecho, en esta Facultad (Primer Semestre de 1997)